A study on the pigment bixin, a pigment present in Bixa orellana L. (Fam. Bixaceae) - Atangan, Ami A.
The coloring substance in the seeds of Bixa orellana L. (Fam. Bixaceae) was extracted following the procedure suggested by Koolhas. Dark red crystals were obtained from the extract. Thin layer chromatography procedures in silica gel G were done to determine the appropriate solvent system. Single solvent systems were first utilized to determine which solvent would produce the best elution. Yellow and yellow-orange spots were obtained with the former being more eluted than the latter. The best solvent system was found to be methanol-chloroform (1:1) wherein the yellow principle was separated from the yellow-orange spot. The yellow spot had an average Rf value of 0.93 and the yellow-orange spot Rf value of 0.80. on dissolving the crystals in absolute methanol (A.R.) and subjecting to UV spectrophotometric analysis, absorbance was read at λmax = 208 with a shoulder peak at λ = 209 nm.